2018
DOI: 10.1101/393579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cbsoverdosage is necessary and sufficient to induce cognitive phenotypes in mouse models of Down syndrome and interacts genetically withDyrk1a

Abstract: 26Identifying dosage sensitive genes is a key to understand the mechanisms 27 underlying intellectual disability in Down syndrome (DS). The Dp(17Abcg1-Cbs)1Yah 28 DS mouse model (Dp1Yah) show cognitive phenotype and needs to be investigated 29 to identify the main genetic driver. Here, we report that, in the Dp1Yah mice, 3 copies 30 of the Cystathionine-beta-synthase gene (Cbs) are necessary to observe a deficit in 31 the novel object recognition (NOR) paradigm. Moreover, the overexpression of Cbs 32 alone is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Undeniably we should work with the whole set of genes homologous to Hsa21, either bringing together all the trisomies/duplication of regions homologous to Hsa21 in mouse and rats or use transchromosomic mice. This is supported by recent data showing an epistatic interaction between Dyrk1a and Cbs, located respectively on the Mmu16 and the Mmu17 homologous regions (Marechal et al, 2019b). Thus, it is really a challenge to get together DS models for the 3 chromosomal regions.…”
Section: Future and Perspectivesmentioning
confidence: 74%
See 4 more Smart Citations
“…Undeniably we should work with the whole set of genes homologous to Hsa21, either bringing together all the trisomies/duplication of regions homologous to Hsa21 in mouse and rats or use transchromosomic mice. This is supported by recent data showing an epistatic interaction between Dyrk1a and Cbs, located respectively on the Mmu16 and the Mmu17 homologous regions (Marechal et al, 2019b). Thus, it is really a challenge to get together DS models for the 3 chromosomal regions.…”
Section: Future and Perspectivesmentioning
confidence: 74%
“…They further showed that, when adding trisomy of the Mmu17 region to the Dp(16)1Yey model, the rescue of the deficit observed in the Dp(16)1Yey model by crossing with Ms1Rhr mice was no longer observed, suggesting epistatic interactions between trisomic genes on Mmu17 and trisomic Mmu16 genes (Zhang et al, 2014). Our laboratory went further in deciphering the genes behind such epistatic interaction with Cbs found on Mmu17 and Dyrk1a on Mmu16 for their impact on DS-related memory deficits (Marechal et al, 2019b).…”
Section: Iii12 Dissecting Ds Using a Compendium Of Mouse Modelsmentioning
confidence: 83%
See 3 more Smart Citations